2023
DOI: 10.1136/bmjgast-2022-001003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct transcriptional signatures in purified circulating immune cells drive heterogeneity in disease location in IBD

Abstract: ObjectiveTo infer potential mechanisms driving disease subtypes among patients with inflammatory bowel disease (IBD), we profiled the transcriptome of purified circulating monocytes and CD4 T-cells.DesignRNA extracted from purified monocytes and CD4 T-cells derived from the peripheral blood of 125 endoscopically active patients with IBD was sequenced using Illumina HiSeq 4000NGS. We used complementary supervised and unsupervised analytical methods to infer gene expression signatures associated with demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Tubulin beta class IIa (TUBB2A) is encoded in the 10q24.2 locus, which plays a crucial role in cell division, cell motility, intracellular transport, and immunomodulatory processes [ 29 ]. Increased TUBB2A expression has been reported in intestinal cells during inflammation-associated bowel disease, thus highlighting its potential as a therapeutic target in immune modulation [ 30 ]. Peroxisome proliferator-activated receptor gamma (PPARG) is a transcription factor located on 3p25.2 [ 31 ] that is involved in regulating macrophage polarization, lipid metabolism and inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin beta class IIa (TUBB2A) is encoded in the 10q24.2 locus, which plays a crucial role in cell division, cell motility, intracellular transport, and immunomodulatory processes [ 29 ]. Increased TUBB2A expression has been reported in intestinal cells during inflammation-associated bowel disease, thus highlighting its potential as a therapeutic target in immune modulation [ 30 ]. Peroxisome proliferator-activated receptor gamma (PPARG) is a transcription factor located on 3p25.2 [ 31 ] that is involved in regulating macrophage polarization, lipid metabolism and inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biomarker-based dietary intervention could offer an additional non-immunosuppressive treatment option for patients [ 21 , 22 ]. Consequently, a currently unmet need is to identify, evaluate and implement promising IBD biomarkers in personalised medicine [ 16 , 17 , 18 ].…”
Section: Identifying Biomarkers Based On Diet–gut Microbes–patient In...mentioning
confidence: 99%
“…Since 2019, cutting-edge research has demonstrated that the effects of diet depend on patient factors and gut microbial activity. Furthermore, a range of biomarker candidates have been identified that need evaluation for clinical translational potential [ 16 , 17 , 18 ]. This review synthesises the newest published research and provides the latest understanding of the relationship between diet, gut microbes and the immune system of the gut barrier ( Box 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Epstein–Barr-virus-induced gene 2 (EBI2, also known as GPR183) is a rhodopsin-like G protein-coupled receptor consisting of 361 amino acid residues . It is exclusively coupled to the Gα i protein, and the cholesterol oxidative metabolite, 7α,25-dihydroxycholesterol (7α,25-OHC), has been found as its most potent endogenous ligand. , GPR183 acts as a chemotactic GPCR highly expressed in immune cells, including B cells, T cells, dendritic cells (DCs), monocytes/macrophages, and innate lymphoid cells. Due to the significance of cholesterol and its metabolites in many fundamental physiological processes, especially as important signaling molecules in the innate and adaptive immune system, the axis of GPR183/7α,25-OHC has been closely implicated in the pathogenesis of many inflammatory and autoimmune diseases, including inflammatory bowel disease (IBD). …”
Section: Introductionmentioning
confidence: 99%